Defensive rebounds discriminate winners from losers in European but not in Asian women`s basketball championships - Madarame, H. (Asian Journal of Sports Medicine, 2018)
Background: Asian national teams have not performed well compared to American and European teams at international competitions in basketball, possibly due in part to anthropometric disadvantages such as shorter height and wingspan. However, although anthropometric disadvantages exist in women as well as in men, Asian women have shown better performances in international competitions than Asian men. Therefore, Asian women might have developed unique strategy and tactics which would be reflected in game-related statistics.